A REVIEW OF CRIMINAL PROFILING PERSPECTIVE LITERATURE - Farah Syaufika; Febrina Pinkan, Roger Clinton P, Tugimin Supriyadi (CV. Adiba Aisha Amira, 2024)
Criminal profiling is a method that combines forensic science, criminology, and psychology to create a profile of the perpetrator that can assist in the investigation process. This technique has been the subject of research in recent decades, particularly in relation to serious crimes such as serial murder and sexual assault. Criminal profiling helps law enforcement understand the nature and behavioral patterns of offenders to predict their next actions and create better arrest plans. However, academics and practitioners still debate its effectiveness. This research uses the literature review method by collecting and analyzing 10 journals related to criminal profiling. This study aims to provide a comprehensive analysis of the advantages and disadvantages of criminal profiling methods in law enforcement, with an emphasis on the importance of the validity and credibility of these methods. This research will also discuss the theoretical basis of criminal profiling, techniques, and its application in various contexts.